Die Europäische Union auf dem Weg zur Verfassungsrechtsgemeinschaft. Vortrag auf dem Kölner Symposium "50 Jahre Römische Verträge" am 13. April 2007 - Stern, Klaus (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2010)
Even though the history of European unification has its origins in the economic sector, the integration process was also a political one from the beginning. The Treaty of Rome already contained elements of constitutionalisation and the designation of the Treaty as a constitution became more and more common among legal scholars since the 1960s, although this has always been controversial. Irrespective of the dispute about the term “Constitution”, the legal order which has been established with the treaties has constitutional character at least in substance. It contains rules that one regularly associates with national constitutions. European integration has always been shaped by constitutional ideals, hence one can call the member states a constitutional community. Important steps forward in the constitutionalisation process were the convention method and the production of the Charter of Fundamental Rights. The Draft Constitutional Treaty for Europe continued this process. As it embodies typical elements of a Constitution, the Treaty deserves its name. It should lay the foundations for a clear, coherent and concise constitutional text which could then further reform and integration in Europe and could be an instrument for identity construction.